The translation in Mexico of Juarez und Maximilian by Franz Werfel (2021)
This article presents and analyzes the two translations into Spanish of the work published in Mexico Juarez und Maximilian by the Austrian writer Franz Werfel. The analysis is carried out from the cultural semiotics, the communication theory exposed by Göran Sonesson and the negotiation process by Umberto Eco. The complexity of these translations can be found in two aspects: first, it is a work that passed from the German to English and from there to Spanish, but also from German to Spanish; and second, the required knowledge of Mexico’s history to achieve its understanding. As a result, it is possible to distinguish between the discourses of each of the target texts and the base text, as well as their relationship with the biographical features of the translators and their cultural competencies, and the usage of the target texts.